The Effect of Dhikr on The Emergence of Somatoform Disorders During Distance Learning in The 2019 Batch of Yarsi Medical Students And A Review According to Islamic View - Rasyid, Naufal; Dian Maharsi, Eri; Arsyad, Muhammad (Junior Medical Journal, 2025)
Background: The impact of Distance learning (DL) during the COVID-19 pandemic on students causes anxiety disorders, excessive worry, and feeling depressed. Meditation or mindfulness is one method to treat a mental disorder. Purposes:This study aimed to determine the relationship between dhikr and the occurrence of somatoform disorders among Yarsi medical faculty students during distance learning. Method: The type of research was descriptive observational with a cross-sectional approach. The study population was YARSI medical students in the 2019 batch, and purposive sampling was conducted. The inclusion criteria were medical students in the 2019 batch who were active and did dhikr, while the exclusion criteria were medical students in the 2019 batch who are not active and not doing dhikr. The tool used in this study was a questionnaire adapted from The Somatic Symptom Scale-8. The data are analyzed univariately and bivariately using SPSS Result: 90.2% of respondents carry out DL for 5-9 hours per day; those who liked DL were 59.7%, and those who did not like DL were 40.2%. Respondents who experienced stress were 96.3%, and 100% percent of respondents had a good perception of dhikr. Respondents who consistently did dhikr were 82.9%. There was no relationship between dzikir and the appearance of somatoform disorders because the P value of the Chi-square test was 0.0079. Conclusion: Respondents mainly experienced mild to severe stress during distance learning, even though the dhikr respondents' perceptions were good. There is no correlation between dhikr and the appearance of somatoform disorder.